Hcprismatin-14 of Hyriopsis cumingii, a novel matrix protein is crucial for framework recognition and crystal deposition during prismatic layer formation - Jin, Can; Zhang, Yihang; Cheng, Kang; Jiang, Rui; Jiang, Shangning; Shi, Yezhong; Ren, Gang; Luo, Wen (Frontiers in Marine Science, 2023)
Mollusk shells are characterized by hierarchical aggregation of calcium carbonate and organic matrix, and matrix protein is considered as a key active ingredient to understand shell biomineralization. In this study, a total of 21 proteins, including a novel matrix protein Hcprismatin-14 were identified in the EDTA-soluble matrix of the prismatic layer of the mussel Hyriopsis cumingii by liquid chromatography tandem mass spectrometry (LC-MS/MS). The full length of Hcprismatin-14 cDNA was cloned from the mantle of H. cumingii. Hcprismatin-14 contains a high proportion of Gly, Tyr, Arg and Asp residues, their concentrated distribution forms three structurally characteristic regions: a Gly/Tyr-rich region, a WDD-repeat region and a C-terminal basic tail. Hcprismatin-14 expression was high in mantle edge tissue in a tissue-specific analysis, and during disordered crystal deposition in a saibo transplantation assay. Knocking down Hcprismatin-14 expression with double-stranded RNA induced subgrains deposition inhibition and lost contact with chitinous scaffold. In addition, the WDD-repeat region polypeptide was involved in morphological regulation of calcite and had dose-dependent inhibitory activity against aragonite deposition in vitro. Based on these results, Hcprismatin-14 appears to be a dual-function prismatic-layer matrix protein, responsible for both framework recognition and crystal deposition. These findings contribute to understanding the relationship between the modular structure of matrix protein and their regulation mechanism during shell biomineralization in mollusks.